2017
DOI: 10.9734/mrji/2017/24508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Potency and Phytochemical Screening of Persea americana Leaf Extracts against Selected Bacterial and Fungal Isolates of Clinical Importance

Abstract: Aim: The quest for novel bioactive from natural sources informed the evaluation of the antimicrobial alongside the phytochemical composition of leaf extracts of Persea americana obtained from Akure, Ondo State, Nigeria. Study Design: This study assessed the prospective antimicrobial efficacy of Persia americana against selected clinically relevant bacteria and fungi. Place and Duration of Study: The study was conducted between April and September, 2015 at the Microbiology 2 Staphylococcus aureus ATCC 43300, Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Acetone extracts have shown noteworthy reduction in the growth of various microbes [33,34]. In other studies [8], the acetone extract was shown to particularly extract tannins, flavonoids, terpenoids, alkaloids, and saponins from P. americana leaves, which may be attributed to the antibacterial activity observed in this study. e antimicrobial activity of extracts from P. americana was evaluated against both Gram-positive (S. epidermidis) and Gram-negative (K. pneumoniae) bacteria.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Acetone extracts have shown noteworthy reduction in the growth of various microbes [33,34]. In other studies [8], the acetone extract was shown to particularly extract tannins, flavonoids, terpenoids, alkaloids, and saponins from P. americana leaves, which may be attributed to the antibacterial activity observed in this study. e antimicrobial activity of extracts from P. americana was evaluated against both Gram-positive (S. epidermidis) and Gram-negative (K. pneumoniae) bacteria.…”
Section: Discussionsupporting
confidence: 69%
“…Different parts of the plant have received remarks for their therapeutic effects against skin infections, stomachaches, anaemia, skin ulcers, and diabetes [7]. Ajayi et al [8] evaluated the effects of methanolic leaf extracts of P. americana against clinical strains of Escherichia coli and Pseudomonas aeruginosa. e study showed that the extracts possess potent antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemicals screenings of Avocado showed the presence of saponins, phytosterols tannins, polyphenols, alkaloidscarotenoids, tocopherols, and terpenoids as themain bioactive components in the extract of leaves, fruit, pulp, and roots, which may explain the reported inhibitory activity from this work and many other similar works. [17][18][19] This result provided a kinetic basis on the findings that Avocado contains nutrients and bioactive compounds that showed an anti-obesity effect, therefore, helps in reducing the risk of becoming overweight/obese. 20,21 It also serves as nutraceuticals against obesity.…”
Section: Resultsmentioning
confidence: 65%
“…These compounds belong to the hydroxycinnamic acid and hydroxybenzoic acid families. Furthermore, saponins, steroids, terpenes, tannins, alkaloids, flavonoids, terpenoids, and cardiac glycosides have been detected in leaf and seed extracts of P. americana obtained with methanol, acetone, and ethyl acetate [ 62 , 63 ]. Although it is clear that the composition depends on the type of extraction.…”
Section: Discussionmentioning
confidence: 99%